Accelerating Blockchain Transaction Verification With Parallel Computing - Zhou, Huangjin (2024)
A Master of Science thesis in Computer Engineering by Huangjin Zhou entitled, “Accelerating Blockchain Transaction Verification with Parallel Computing”, submitted in May 2024. Thesis advisor is Dr. Gerassimos Barlas. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).